The study case of employees motivation at Marudi District Office / Abdul Kadir Said Malim - Said Malim, Abdul Kadir (2007)
Motivation has become a major concern in recent years through out MalaysiaGovernment Agencies. Therefore, it is important to identify the determinants of motivation and hygience factorss for the employees and to establish the impact to the workplaces. This study focused on investigating whether the employees of Marudi District Council are more satisfied with their work environment and the reasons for this. Data were drawn from the questionnaire of 115 of employees and analyses using limited dependent variable techniques. Motivation is an attitude that employees have about their work and is based on numerous factors, both intrinsic and extrinsic to the individual. There have some factors to maintain the satisfaction among the employees such as clear company administrative policies should be developed, supervision from the management or superior, salary, interpersonal relations and the working conditions.